The Virtual Reality Lab: Realization and Application of Virtual Sound Environments. (November 2020) - Hohmann, Volker; Paluch, Richard; Krueger, Melanie; Meis, Markus; Grimm, Giso
Abstract : To assess perception with and performance of modern and future hearing devices with advanced adaptive signal processing capabilities, novel evaluation methods are required that go beyond already established methods. These novel methods will simulate to a certain extent the complexity and variability of acoustic conditions and acoustic communication styles in real life. This article discusses the current state and the perspectives of virtual reality technology use in the lab for designing complex audiovisual communication environments for hearing assessment and hearing device design and evaluation. In an effort to increase the ecological validity of lab experiments, that is, to increase the degree to which lab data reflect real-life hearing-related function, and to support the development of improved hearing-related procedures and interventions, this virtual reality lab marks a transition from conventional (audio-only) lab experiments to the field. The first part of the article introduces and discusses the notion of the communication loop as a theoretical basis for understanding the factors that are relevant for acoustic communication in real life. From this, requirements are derived that allow an assessment of the extent to which a virtual reality lab reflects these factors, and which may be used as a proxy for ecological validity. The most important factor of real-life communication identified is a closed communication loop among the actively behaving participants. The second part of the article gives an overview of the current developments towards a virtual reality lab at Oldenburg University that aims at interactive and reproducible testing of subjects with and without hearing devices in challenging communication conditions. The extent to which the virtual reality lab in its current state meets the requirements defined in the first part is discussed, along with its limitations and potential further developments. Finally, data are presented from a qualitative study that compared subject behavior and performance in two audiovisual environments presented in the virtual reality lab—a street and a cafeteria—with the corresponding field environments. The results show similarities and differences in subject behavior and performance between the lab and the field, indicating that the virtual reality lab in its current state marks a step towards more ecological validity in lab-based hearing and hearing device research, but requires further development towards higher levels of ecological validity.